Implementação de um modelo de triagem cirúrgica para casos urgentes em um hospital terciário - Coelho, Monique Antonia [UNESP]; Lourenção, Pedro Luiz Toledo de Arruda [UNESP]; Weber, Silke Tereza [UNESP]; Ortolan, Erika Veruska Paiva [UNESP] (FapUNIFESP (SciELO), 2019)
OBJECTIVE: to evaluate the applicability of the Timing of Acute Care Surgery (TACS) color classification system in a tertiary public hospital of a developing country. METHODS: we conducted a longitudinal, retrospective study in a single center, from March to August 2016 and the same period in 2017. We opted for the selection of four surgical specialties with high demand for emergencies, previously trained on the TACS system. For comparisons with the previous classifications, we considered emergencies as reds and oranges and urgencies, as yellow, with an ideal time interval for surgery of one hour and six hours, respectively. RESULTS: non-elective procedures accounted for 61% of the total number of surgeries. The red, orange and yellow classifications were predominant. There was a significant improvement in the time before surgery in the yellow color after the TACS system. Day and night periods influenced the results, with better ones during the night. CONCLUSION: this is the first study to use the TACS system in the daily routine of an operating room. The TACS system improved the time of attendance of surgeries classified as yellow.

OBJETIVO: avaliar a aplicabilidade do sistema de classificação de cores Timing of Acute Care Surgery (TACS) em um hospital público terciário de um país em desenvolvimento. MÉTODOS: estudo longitudinal, retrospectivo, de um único centro, de março a agosto de 2016 e o mesmo período em 2017. Optou-se pela seleção de quatro especialidades cirúrgicas com alta demanda de urgências, as quais foram previamente treinadas sobre o sistema TACS. Para comparação com as classificações prévias de urgência e emergência, emergências foram consideradas como vermelhas e laranjas e urgências como amarelas, com intervalo de tempo ideal para cirurgia de uma hora e de seis horas, respectivamente. RESULTADOS: os procedimentos não eletivos representaram 61% do número total de cirurgias. As classificações vermelha, laranja e amarela foram predominantes. Houve melhora significativa do tempo para a cirurgia na cor amarela após o sistema TACS. Períodos diurnos e noturnos influenciaram os resultados, com melhores resultados durante o período noturno. CONCLUSÃO: este é o primeiro estudo que usou o sistema TACS no dia a dia de um centro cirúrgico, e demonstrou que o sistema TACS melhorou o tempo de atendimento das cirurgias classificadas como amarelas.
Implementation of a surgical screening system for urgent and emergent cases in a tertiary hospital